Inequality and the global economic crisis / Douglas Dowd. - Dowd, Douglas Fitzgerald, 1919- (London ; New York : Pluto Press ; New York : Distributed in the United States of America exclusively by Palgrave Macmillan, 2009)
Inequality has always been with us. With the growth of capitalism ac ross the globe, inequalities of income, wealth and power became increas ingly extreme. Written by economist Douglas Dowd, this book shows that the present banking crisis is the result of the growth of inequality ac ross the globe. The expansion of the financial sector has brought incre dible riches to a select few, at the expense of the majority. Inequalit y was ignored, or described as a necessary aspect of a booming global e conomy. With the collapse of the world markets, the fallacy of this pos ition is clear. Inequality and the Global Economic Crisis shows how it is only by addressing inequality that we can secure the health of our e conomies in the future.--Publisher.
Includes bibliographical references (p. 271-282) and index.
Keywords: Financial crises; Income distribution; Equality -- Economic aspects; Globalization -- Economic aspects; Capitalism; Poverty